Antiepileptic drug discontinuation by people with epilepsy in the general population. (26th July 2017) - Giussani, Giorgia; Bianchi, Elisa; Canelli, Valentina; Erba, Giuseppe; Franchi, Carlotta; Nobili, Alessandro; Sander, Josemir W.; Beghi, Ettore; ,
Summary: Objective: Rate, reasons, and predictors of antiepileptic drug (AED) discontinuation were investigated in a well‐defined cohort of people with epilepsy to verify efficacy and tolerability of treatment up to 20 years from treatment initiation. Methods: The history of AED usage in children and adults with epilepsy registered with 123 family physicians in an area of Northern Italy between 2000 and 2008 was recorded. Cumulative probabilities of AED withdrawal for specific reasons were estimated using cumulative incidence functions. The probabilities of withdrawing for terminal remission, and of achieving sustained remission while still on treatment, were also evaluated. The roles of sex, age at diagnosis, seizure types, duration at diagnosis, and syndrome were assessed with hazard ratios and 95% confidence intervals. Results: Seven hundred thirty‐one of 747 individuals were treated with one or more AEDs during the disease course. The three commonest drugs were valproate, carbamazepine, and phenobarbital. Reported reasons for AED withdrawal were, in decreasing order, terminal remission, ineffectiveness, and adverse events. The probability of withdrawing the first AED for terminal remission was 1.0% at 1 year and increased to 20.0% at 20 years. Corresponding rates were 2.9% and 12.6% for ineffectiveness and 0.5% and 3.3% for adverse events. Reasons for withdrawal varied with individuals' age, sex, disease characteristics, and drugs. Significance: The initial AED given was retained in the majority of cases. Terminal remission, lack of efficacy, and adverse effects were, in decreasing order, the commonest reasons for AED discontinuation. Withdrawal could be predicted by age at diagnosis, sex, and clinical characteristics and varies among drugs.